PERTUMBUHAN, PRODUKSI DAN TOLERANSI VARIETAS JAGUNG (Zea may L.) PADA TANAH GAMBUT HEMIK - Haryoko, Widodo; Mutia, Yopa Dwi; Thesiwati, Aslan Sari; Utama, M. Zulman Harja; Hariyanto, Peri (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Corn is a highly adaptable plant and can be cultivated in various soil fertility conditions.  Testing of corn varieties on hemic peat soils and while maintaining hydrological function is still very limited so that there is a void of information about corn varieties tolerant of toxic organic acids in hemic peat soils. The purpose of the experiment was to determine the growth, production and tolerance of corn varieties on hemic peat soils. The experiment was conducted using a complete randomized design by testing 4 varieties of corn namely Pioneer 23, NK 22, Bisi 18 and Pertiwi 3 repeated 5 times.  The experimental results showed that the Bisi 18 corn variety and Pertiwi 3 variety with production of 7.66 and 7.68 t ha-1 respectively.showed greater STI in hemik peat rice fields with high levels of toxic organic acids than STI Pioneer 23 variety and NK 22 variety with production of 7.48 and 7.53 t ha-1 respectively.